Narratives of Disillusionment: A Phenomenological Study on Consumer Experiences With Inconsistent Sustainability Claims - Fitriyana, Elvira (Generate Digital Publishing, 2025)
Objective: This research aims to explore the role of authentic narratives in sustainability marketing and their impact on consumer trust, loyalty and cultural consumption patterns. The research focuses on how consistency in sustainability claims and transparent communication influence consumer perceptions, especially among younger generations such as Millennials and Gen Z. Research Design & Methods: This phenomenological study explored consumers' experiences with inconsistent sustainability claims through in-depth interviews and a review of greenwashing-related literature. Thematic analysis identified key themes such as disappointment, distrust and the impact on purchasing behaviour. Findings: The findings reveal that authentic narratives increase consumer trust, reduce scepticism and drive brand loyalty by 42% when aligned with company actions. Consistent communication increased Gen Z recommendations by 30%, while inconsistent claims decreased purchase intent by 35%. Implications & Recommendations: Companies should adopt authentic narratives in marketing that are aligned with sustainability actions. Regulators need to establish a framework to monitor and certify sustainability claims to address greenwashing. Contribution & Value Added: This study fills the literature gap by integrating insights on authentic narratives and sustainable marketing. This research offers a framework for practitioners to implement marketing strategies that align with consumer values, supporting the cultural shift towards sustainable consumption.